The role of consumer participation readiness in automated parcel station usage intentions. (May 2020) - Chen, Ching-Fu; White, Christopher; Hsieh, Yi-En
Abstract: Automated parcel stations (APS) offer an effective and efficient way to respond to increasing volumes of online commerce and to add value to traditional 'last mile' parcel pick-up and delivery options. We developed a theoretical sound model with consumer participation readiness (CPR) as the foundation construct and showed that technology anxiety and service convenience fully mediate the effects of CPR on usage intentions. The model explained over 80% of the variance in the dependant variable and our findings offer novel insights that have important theoretical and managerial implications.